Empowerment of Eucalyptus Oil Farmer Groups Through Training in The Use of Social Media for Product Marketing - Hentihu, Idrus; Hamid, Iskandar; Bula, Muhammad; Taufik, Muhammad; Faradilla, RH Fitri (Pascasarjana Universitas Mataram, 2024)
In Buru Regency, Waimiting Village is one of the eucalyptus oil processing centers. Processed eucalyptus oil products still have obstacles in marketing management in the community. The lack of optimization of farmers' marketing management institutions has had an economic impact on farmers' welfare. Therefore, training on the use of social media for marketing eucalyptus oil products is important to be carried out to increase the empowerment of farmers in fulfilling income which then leads to the welfare of farmers. The objective of this program is to support the growth of small businesses owned by a group of social entrepreneurship-based entrepreneurs and eucalyptus oil distillation centers. The research was conducted using participatory surveys, observations, lectures, discussions, and silent practice, involving about 12 people who are members of the